Estrategias utilizadas en el sector hotelero de la zona centro y terminal de la ciudad de Villavicencio como respuesta a la reactivación económica (2023)
The document describes as a general objective to identify the strategies implemented in the hotel sector of the downtown and terminal area of the city of Villavicencio. The methodology was qualitative, with a descriptive approach; it was estimated to work with the hotel sector of the city of Villavicencio and the sample consists of 35 hotels located in the terminal sector and the downtown area, who responded to the semi-structured survey voluntarily. The results showed how the behavior of the hotel sector was after the economic reactivation of the supply and demand cycle, observing that compared to the national consolidated the region of Los Llanos – Orinoquia reached a recovery of 10.4% compared to 2021. In relation to the attributes of attention and quality service, in addition to generating an assertive communication route, also to establish promotions, alliances and schemes that lead to understanding the needs of the client and offering the service. Finally, the perception of the administrators led to observe the affectation generated after the reduction of income, in addition to expressing that they did not receive support from State entities: on the other hand, they chose to refinance the obligations to stay in the market. They also mentioned that they resorted to the positioning strategy or reputation of the company name which refers to the choice and trust that customers placed in each of the hotels to configure promotion plans and establish a path of continuous improvement. KEY WORDS: strategies, hotel sector, Villavicencio.